Crimes in Višegrad. The Criminal Responsibility of Milan Lukić before the International Criminal Tribunal for the Former Yugoslavia - Żarna, Krzysztof (Polityka i Społeczeństwo, 2025)
The aim of this article is to present the phenomenon of ethnic cleansing in the eastern part of Bosnia and Herzegovina, using the case of Višegrad as an example. A key role in the extermination of Bosniak Muslims was played by members of Serbian paramilitary organisations and police forces. Their effectiveness in these actions was largely due to their familiarity with the region and the local population. The individual responsible for organising the ethnic cleansing in the Višegrad area was Milan Lukić, the leader of the paramilitary group White Eagles. He was accountable for crimes against humanity targeting Bosniak Muslims, which ultimately led to a complete change in the ethnic structure of the region. This study outlines the entire process of bringing Milan Lukić to justice before the International Criminal Tribunal for the Former Yugoslavia. The article employs a case study method and content analysis.